2022
DOI: 10.1111/cdev.13811
|View full text |Cite
|
Sign up to set email alerts
|

Emotional quality of early education programs improves language learning: A within‐child across context design

Abstract: Observational studies comparing child outcomes in early care and education classrooms of differing quality are often confounded by between‐child differences. A within‐child design, tracking children across contexts, can identify the effects of quality with less confounding. An analysis of Australian children (N = 1128, mean age 5 years, 48% female, 2.9% Indigenous, ethnicity data unavailable) tracked across pre‐K, K, and year 1 (2010–2012) was conducted to assess how changes in observed quality (Classroom Asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 94 publications
0
3
0
1
Order By: Relevance
“…Although this may have been because educators had conflated research-related paperwork with the CP3 itself, this aspect remains important. Research in the early childhood education sector has highlighted that issues such as paperwork are a major impediment to workplace well-being and the educational effectiveness of educators [ 31 ], which can, in turn, influence the quality of OSHC service provision and child outcomes [ 32 , 33 ]. The digitization of CP3 implementation and support tools is planned to minimize the administrative burden of the CP3.…”
Section: Discussionmentioning
confidence: 99%
“…Although this may have been because educators had conflated research-related paperwork with the CP3 itself, this aspect remains important. Research in the early childhood education sector has highlighted that issues such as paperwork are a major impediment to workplace well-being and the educational effectiveness of educators [ 31 ], which can, in turn, influence the quality of OSHC service provision and child outcomes [ 32 , 33 ]. The digitization of CP3 implementation and support tools is planned to minimize the administrative burden of the CP3.…”
Section: Discussionmentioning
confidence: 99%
“…Second, in-person observations can be prohibitively expensive to implement, as these require on-site (or virtual) human personnel to conduct such observations (Pianta and Hamre, 2009 ). Consequently, larger-scale studies of children's language experiences often rely on infrequent, brief observations of children, upon which generalizations are drawn (Rankin et al, 2022 ; Vitiello et al, 2022 ). For instance, in a study of the effectiveness of teacher-child instructional interactions, Cabell et al ( 2013 ) analyzed data derived from a single observation conducted in each of 314 preschool classrooms.…”
Section: Accuracy Of Automated Processing Of Child and Adult Language...mentioning
confidence: 99%
“…As a national indicator of quality, NQS quality assessment data provide information that informs policy and holds services accountable. However, research has indicated a mismatch between NQS quality ratings and quality when assessed with quality rating scales frequently used in research (Siraj et al, 2019;Kirk et al, 2022;Rankin et al, 2022). Indeed, Siraj et al (2019) report that NQS quality ratings of exceeding the NQS (the highest rating) align with basic levels of quality on average when compared with evidence-based environmental rating scales designed to directly measure elements of curriculum, pedagogy and practice linked to high-quality ECEC provision, i.e., ECERS-E (Sylva et al, 2003) and the SSTEW (Siraj et al, 2015).…”
Section: The National Quality Standardmentioning
confidence: 99%